Evaluation of selected papaya lines for the preservation of desirable traits - Álvarez-Hernández, Juan Carlos; Castillo-Martínez, Carlos Román; Apaez-Barrios, Maricela (Revista Mexicana de Ciencias Agrícolas, 2024)
There are currently few varieties of papaya in Mexico and the dominant one is ‘Maradol’, which over time has been vulnerable. Nonetheless, developing varieties for seed production is challenging. The objective was to evaluate outstanding and adapted papaya lines for the conservation of desirable traits. In the field, 23 lines of the ‘Maradol’ type were evaluated in Antúnez Michoacán, Mexico, in 2022. Initially, plant height, stem circumference, number of leaves and height to first fruit were recorded. During plant development, outstanding plants were identified and their pollination was controlled. In developed fruits, polar and equatorial circumference, weight, width and firmness of the pulp, and soluble solids were recorded. The development of plants presented differences, whose variability between lines allowed the identification of morphological characteristics of interest. Only 10 lines had this condition. In pollination control, the number of fruits formed over the flower buds decreased and the fruits collected over the fruits formed decreased. The characterization of fruits, except for soluble solids, showed differences. Multivariate analysis indicated variability associated with each principal component. It is concluded that of 23 papaya lines, only 43.48% presented outstanding plants. Within the lines, between 5 and 10% of the plants were selected. In the pollination control, they tended to decreased among the stages since only 28% of fruits were obtained. The selected lines showed fruit variability.
Keywords: Carica papaya; hermaphrodite; ‘maradol’ genotype; plant sexing